Evaluating Changes in Determinants of Stunting among Children Under 2 Years and Assessing Their Contribution to Socioeconomic Disparity in Child Nutritional Status across India - Deboshree Das (Wolters Kluwer Medknow Publications, 2022)
Background: Despite concentrated global efforts to bring about reduction in malnutrition among children, it continues to remain a public health concern, especially in developing countries such as India. While substantial reduction in the levels of stunting has taken place over the years, high levels of variation exist in distribution of stunting across the country. Objective: The study aimed to identify the determinants of stunting in early childhood and their contribution to change in levels of stunting across India. It also compared the socioeconomic disparity in the levels of stunting and changes therein over the last decade. Methods: The study utilizes data from the National Family Health Survey (NFHS-3 and NFHS-4) on children aged under-2 years. Bivariate and multivariate logistic regression identified determinants of early childhood stunting followed by Oaxaca decomposition model to assess the contribution of each of the factors to reduction in levels of stunting over the years. Concentration index was used to study the socioeconomic disparity in early childhood stunting. Results: Nearly 19% decrease in early childhood stunting can be attributed to increase in institutional deliveries, 14% to increase in maternal schooling, and 10% to improvement in maternal body mass index. In spite of an overall decrease, very little change is seen in socioeconomic disparity of childhood stunting. Conclusions: The study identifies institutional deliveries, maternal schooling, and maternal health as major contributors of decrease in early childhood stunting. It identifies persisting socioeconomic disparity in childhood stunting over the last decade.